Impact of microRNA polymorphisms on high-dose methotrexate-related hematological toxicities in pediatric acute lymphoblastic leukemia - Zhan, Min; Liu, Ting; Zhang, Zhou; Wang, Guoqiang; Cao, Zhongqiang; Li, Xuejuan; Zeng, Hongwu; Mai, Huirong; Chen, Zebin (Frontiers in Pediatrics, 2023)
Objectives: It is well known that transporter and enzyme genes could be regulated by microRNA (miRNA) at the post-transcriptional level, and single nucleotide polymorphisms (SNPs) in miRNA which is involved in the microRNA production and structure may affect miRNA expression level and then influence drug transport and metabolism. In this study, we aim to evaluate the association between miRNA polymorphisms and high-dose methotrexate (HD-MTX) hematological toxicities in Chinese pediatric patients with acute lymphoblastic leukemia (ALL). Method: 654 evaluable cycles of HD-MTX were administrated to 181 children with ALL. Their hematological toxicities were evaluated according to NCI-CTCAE v5. The association between 15 candidate SNPs of miRNA and hematological toxicities (leukopenia, anemia, thrombocytopenia) was analyzed by Fisher’s exact test. Further multiple backward logistic regression analysis was used to explore the independent risk factor of grade 3/4 hematological toxicities. Result: Rs2114358 G>A in pre-hsa-miR-1206 was related to HD-MTX-related grade 3/4 leukopenia after multiple logistic regression (GA+AA vs GG: OR 2.308, 95% CI: 1.219-4.372, P = 0.010), and rs56103835 T>C in pre-hsa-mir-323b was associated with HD-MTX-related grade 3/4 anemia (TT+TC vs CC: OR 0.360, 95% CI: 0.239 - 0.541, P = 0.000), none of the SNPs significantly associated with grade 3/4 thrombocytopenia. Bioinformatics tools predicted that rs2114358 G>A and rs56103835 T>C would have effect on the secondary structure of pre-miR-1206 and pre-miR-323b respectively, and then probably changed the expression level of mature miRNA and theirs’s target genes. Conclusion: Rs2114358 G>A and rs56103835 T>C polymorphism may potentially influence HD-MTX-related hematological toxicities, which may serve as candidate clinical biomarkers to predict grade 3/4 hematological toxicities in pediatric patients with ALL.